Methodological approach and principles of research activity development of university teachers based on action research - Берикханова, А.Е.; Сарсенбаева, Л.О.; Сапаргалиева, Б.О.; Ибраимова, Жанар (Pedagogy and Psychology, 2023)
The article is devoted to the problem of developing the research activity of university teachers based on the integration of the Action Research approach into professional practice. The relevance of improving the quality of education by involving teachers in research activities with the involvement of internal resources of professional practice is substantiated. The methodological approaches underlying the development of research activity (activity, synergetic) are considered.An analysis of modern research is given, revealing modern technologies for the formation of research competencies of teachers. The possibilities of the Action Research method in the development of the research activity of teachers are revealed. The principles for the development of research activity (proactivity, self-reflection, creativity, self-development and self-realization, continuity, integration of all types of educational activities, actualization of learning resources, synergy of efforts of the subjects of the educational process) are formulated. Prospects for integrating Action Research into the educational practice of universities are shown.